2015
DOI: 10.1111/jvp.12235
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of pimobendan enantiomers after oral and intravenous administration of racemate pimobendan formulations in healthy dogs

Abstract: Pimobendan is a benzimidazole-pyridazinone derivative, marketed as a racemic mixture for the management of canine heart failure. Pharmacokinetics of the enantiomers of pimobendan and its oral bioavailability have not been described in dogs. The aim of this study was to describe pharmacokinetics of three formulations of pimobendan in healthy dogs: the licensed capsule product, and novel liquid and intravenous formulations. A three-period, nested randomized two-treatment crossover design was used. Pimobendan was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 16 publications
4
37
0
Order By: Relevance
“…However, the therapeutic efficacy of the plasma concentrations reported in our study is difficult to interpret, partly because the plasma concentrations associated with the presumed efficacy of PIM and OMDP are not clearly defined in dogs. The authors noticed a disparity among the pharmacokinetic profiles of pimobendan reported by others (1,6,21). The key pharmacokinetic parameters of PIM and ODMP from different studies are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…However, the therapeutic efficacy of the plasma concentrations reported in our study is difficult to interpret, partly because the plasma concentrations associated with the presumed efficacy of PIM and OMDP are not clearly defined in dogs. The authors noticed a disparity among the pharmacokinetic profiles of pimobendan reported by others (1,6,21). The key pharmacokinetic parameters of PIM and ODMP from different studies are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 92%
“…The key pharmacokinetic parameters of PIM and ODMP from different studies are summarized in Table 2 . Pimobendan capsule 0.25 mg/kg resulted in a C max of 38.1 ± 18.3 ng/ml ( 1 ). In two other studies, both using pimobendan suspensions (but different products), 0.27 mg/kg of a pimobendan suspension produced C max of 18.6 ng/ml (6.1–25.3), yet 0.3 mg/kg resulted in a C max of 7.3 ± 2.7 ng/ml ( 6 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations